Differences in upper body strength and power between international and national level water polo players - Young, K. P.; Sheppard, J. M.; Haff, G. G.; Newton, R. U.; Watts, D. G.; Daley, S. (Journal of Australian Strength and Conditioning, 2013)
Water polo is an intermittent sport comprised of intense bursts of swimming and wrestling interspersed with low to moderate intensity swimming (13, 16). As a result, players have to develop the appropriate strength and power characteristics to succeed at the elite level. Previous research on elite water polo players has primarily focused on the physiological and fitness characteristics (15, 16) while overlooking the importance of strength and power measures. The ability to produce high levels of strength and power has been shown to clearly discriminate between players of different playing ability in a variety of sports (2, 3, 11). However, no data has been collected that directly compares upper body strength and power measures among elite male water polo players. Therefore, the purpose of this study was to compare the upper body strength and power of selected male water polo players using several isoinertial and isometric tests. In addition, a further analysis of playing ability was also performed to determine whether upper body strength and / or power differentiate between international and national level players.